Microbial molybdate reduction to mo-blue by a cyanide-degrading bacterium - Yakasai, Hafeez Muhammad (2017)
Molybdenum, an emerging pollutant, has recently being demonstrated to be toxic to spermatogenesis in several animal models. It is also very toxic to ruminants causing death at very low level (parts per million). Molybdenum is mined as a small byproduct of copper and gold mining in Malaysia. Molybdenum pollution is also found at dumping sites of waste oil lubricant containing molybdenum disulfide, with levels of up to hundreds of parts per million found. Molybdenum, in the soluble form, molybdate can be reduced to molybdenum blue, a colloidal and relatively insoluble product and this phenomenon forms the basis for bioremediation of molybdenum. This research is therefore, aimed at screening, phylogenetic identification, characterization and optimization of molybdenum-reducing activity of the best isolate via one-factorat- a-time (OFAT) and response surface method (RSM); modelling the kinetics of molybdenum reduction through primary and secondary models; finally purify and characterize the molybdenum-reducing enzyme activity. One of the ten previously isolated cyanide-degrading bacteria from gold mine soils in Malaysia exhibited a novel molybdenum reduction to molybdenum-blue, with this best molybdate-reducer further studied on a molybdate low phosphate minimal salts media supplemented with glucose and ammonium sulfate as the carbon and nitrogen source, respectively. Strain HMY3 via phylogenetic analyses reveals that the isolate belongs to Serratia genus. Sucrose was the best carbon source supporting molybdate reduction in this strain and was optimum at 20 g/L. Ammonium sulfate was the best source of nitrogen for strain HMY3 and was optimal at 10 g/L. Strain HMY3 grew best at 35 oC and at pH 6.5. Response Surface Method shows the best conditions for molybdenum reduction were molybdate concentration between 55 and 57.5 mM, phosphate concentration of 3.95 mM, pH 7, sucrose concentration between 15 and 17.5 g/L and incubation time between 48 and 60 h. Molybdenum reduction was inhibited by the heavy metals such as copper, mercury, chromium and arsenic at concentrations higher than 1 ppm. However, prolonged incubation succeeded in overcoming this inhibition. Analysis of the reduction kinetics showed that molybdenum reduction over time can best be modelled using the modified Gompertz model while the reduction kinetics was best modelled using the Luong model. Statistical analysis of these models has been carried out and they exhibit low values for RMSE and AICc, highest adjusted R2 values, Ftest and with Bias Factor and Accuracy Factor nearest to unity (1.0) over other models. The calculated value for the Luong’s constants which are maximal reduction rate, half saturation constant for maximal reduction, maximal concentration of substrate tolerated and curve parameter that defines the steepness of the growth rate decline from the maximum rate symbolized by qmax, Ks, Sm, and n were 0.06±0.1 hr-1, 47.95±10.12 mM, 69.63±0.8 mM and 0.69±0.11, respectively. The Luong model clearly shows strong substrate inhibition to rate of reduction at high substrate (Mo) concentration. The Mo-reducing enzyme has been purified using an ammonium sulfate precipitation followed by gel-filtration chromatography. The results showed that the best ammonium sulfate fraction giving the highest enzyme activity was between 50 and 60% ammonium sulfate concentration. The molybdenum-reducing enzyme was monomeric with an estimated mwt of 105 kDa. The enzyme was further characterized, and the results show that the enzyme is most stable in Tris-buffer pH 7 containing 0.1 mM DTT, temperature 4 oC and not affected by metabolic inhibitors and heavy metals (1 ppm). The enzyme attains optimum catalysis at pH 5.5, temperature between 25 and 35 oC, substrate concentration (LPPM) 12 mM and electron donor (NADH) concentration 5 mM. In conclusion, a novel cyanidedegrading bacterium with a molybdenum reduction capacity has been isolated, and statistical method using RSM has succeeded in optimizing reduction. Also, the enzyme has been purified to homogeneity. The characteristic of this bacterium makes it suitable for future bioremediation works in polluted soil containing cyanide and molybdenum metal.